Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
a. To determine the values of the variable that make the denominators zero, we need to examine the denominators in the given equation:
[tex]\[ \frac{1}{x+2} + 2 = \frac{7}{x+2} \][/tex]
From this equation, we can see that the denominators are [tex]\(x + 2\)[/tex]. We need to find the values of [tex]\(x\)[/tex] that make the denominator zero:
[tex]\[ x + 2 = 0 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ x = -2 \][/tex]
Therefore, the value of the variable that makes the denominator zero is:
[tex]\[ x = -2 \][/tex]
This is our restriction.
b. Next, we solve the equation while keeping in mind the restriction [tex]\(x \neq -2\)[/tex]:
[tex]\[ \frac{1}{x+2} + 2 = \frac{7}{x+2} \][/tex]
To clear the denominators, we can multiply every term by [tex]\(x + 2\)[/tex]:
[tex]\[ (x + 2) \left( \frac{1}{x+2} \right) + 2(x + 2) = (x + 2) \left( \frac{7}{x+2} \right) \][/tex]
This simplifies to:
[tex]\[ 1 + 2(x + 2) = 7 \][/tex]
Expanding and simplifying:
[tex]\[ 1 + 2x + 4 = 7 \][/tex]
[tex]\[ 2x + 5 = 7 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ 2x = 2 \][/tex]
[tex]\[ x = 1 \][/tex]
Therefore, the solution to the equation, keeping the restriction [tex]\(x \neq -2\)[/tex] in mind, is:
[tex]\[ x = 1 \][/tex]
[tex]\[ \frac{1}{x+2} + 2 = \frac{7}{x+2} \][/tex]
From this equation, we can see that the denominators are [tex]\(x + 2\)[/tex]. We need to find the values of [tex]\(x\)[/tex] that make the denominator zero:
[tex]\[ x + 2 = 0 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ x = -2 \][/tex]
Therefore, the value of the variable that makes the denominator zero is:
[tex]\[ x = -2 \][/tex]
This is our restriction.
b. Next, we solve the equation while keeping in mind the restriction [tex]\(x \neq -2\)[/tex]:
[tex]\[ \frac{1}{x+2} + 2 = \frac{7}{x+2} \][/tex]
To clear the denominators, we can multiply every term by [tex]\(x + 2\)[/tex]:
[tex]\[ (x + 2) \left( \frac{1}{x+2} \right) + 2(x + 2) = (x + 2) \left( \frac{7}{x+2} \right) \][/tex]
This simplifies to:
[tex]\[ 1 + 2(x + 2) = 7 \][/tex]
Expanding and simplifying:
[tex]\[ 1 + 2x + 4 = 7 \][/tex]
[tex]\[ 2x + 5 = 7 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ 2x = 2 \][/tex]
[tex]\[ x = 1 \][/tex]
Therefore, the solution to the equation, keeping the restriction [tex]\(x \neq -2\)[/tex] in mind, is:
[tex]\[ x = 1 \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.